Morphological Analysis of Compound Form (Fukugoudoushi) Verb+Ageru in Japanese - Febriliani, Annisa; Rahayu, Ely Triasih; Firmansyah, Dian Bayu (Universitas Pendidikan Indonesia (Indonesia University of Education), 2023)
This study aims to investigate the formation and meaning of fukugoudoushi or compound verb formed from the Verb+ageru. This study is a qualitative descriptive research. The total of 35 data is in the form of sentences in data sources taken from the 2021 edition of the NHK Japan articles. The data collection method is the note-taking method. Data analysis uses the distributional method with advanced techniques for direct elements, namely by dividing the fukugoudoushi forming elements into front and back elements. Furthermore, it explains the characteristics of the front elements based on the theory of Kindaichi (1989) which divides doushi into 4 groups, namely joutaidoushi, keizokudoushi, shunkandoushi, and daiyonshu-doushi. The results showed that out of 35 data analyzed there were front elements of fukugoudoushi ageru in the form of tadoushi-keizokudoushi (20 data), tadoushi-shunkandoushi (9 data), jidoushi-keizokudoushi (1 datum), jidoushi-shunkandoushi (3 data), and futsuumeishi (2 data). The meanings resulting from the formation of fukugoudoushi ageru include showing direction, showing improvement, showing high value, expressing self-demeaning, and ending an activity.